PENGARUH BRAND AWARENESS DAN BRAND PERSONALITY TERHADAP PEMBENTUKAN BRAND IMAGE THE WESTIN RESORT NUSA DUA BALI - Komang Trisna Pratiwi Arcana (Jurnal Ilmiah Hospitality Management, 2014)
The formation of brand image is very important for a company in presenting and expressing the personality of its company. The purpose of this study is to determine the effect of brand awareness and brand personality to the formation of a brand image simultaneously or partially, using multiple regression analysis. This study used data collecting instrument questionnaire and take the sample from 114 employees at Room Division Department, The Westin Resort Nusa Dua Bali. Based on the multiple regression analysis, it is found that the variable of brand awareness and brand personality simultaneous influence on the formation of brand image. Partially, the variable brand awareness and brand personality significantly affecting the formation of brand image. While the most dominant variable to the establishment of brand image is brand awareness’s variable. From these results it is expected that the management of The Westin Resort Nusa Dua Bali keep doing the assessment on how deep the employees understanding on the identity of the company. Then, followed by developing training strategies in which company’s values can be implemented and become an employee’s culture itself.